Modeling HIV/AIDS epidemics in West Africa: Results for UNAIDS modeling approach from some selected countries (2007)
The Estimation and Projection Package (EPP) developed by UNAIDS reference group have been used with some notable success in some countries of the sub-Saharan (East and South) African Countries. In this present studies, we present results for five modeling methods applied to four countries in the West African Sub region. Using five modeling assumption with respect to 2 data situations and paying attention to the parameters determining the dynamics of HIV/AIDS epidemics, we employ Epp to model the prevalence of the epidemic in four West African countries. We used these estimates to further explain the underlying trend in the epidemic in each of the selected countries. For the unedited data, our results shows that in 2005 the default model yielded 17.69% (Urban: 4.72%, Rural: 28.82%) for Nigeria, 5.23% (Urban: 4.48%, Rural: 6.18%) for Ghana, 4.75% (Urban: 5.28%, Rural: 4.33%) for Cote d'Ivoire and 0.54% (Urban: 0.49%, Rural: 0.59%) for Senegal. The computed Log-Likelihood (LL) estimates for the default model are (Urban: 187.8809, Rural: 4, 948. 3913), (Urban: 181.5688, Rural: 664.9529), (Urban: 320.0272, Rural: 388.4773) and (Urban: 45.7742, Rural: 78.0798) for Nigerian, Ghana, Cote d'Ivoire and Senegal, respectively.